PENGALAMAN IMITASI BUDAYA KOREA DALAM SERIAL DRAMA KOREA PADA REMAJA - Nayla Zahra Luthfia; Nurul Hasfi; Amida Yusriana (Interaksi Online, 2023)
This research aims to find out and explore the experience of Korean cultural imitation in Korean drama series in teenagers. The research method used in this study is a qualitative research method with a phenomenological approach. The subjects of this research are adolescents. The theory that is useful as a reference in this research is Modeling Theory by Albert Bandura. From the results of the research conducted on the six informants, they confirmed that they experienced Korean cultural imitation in various Korean drama series. The results of the imitation of the six informants were formed into two cultural categories, namely material culture and nonmaterial culture. Material culture in the form of typical food and typical appearance, and non-material culture in the form of language, and cultural manners in Korea. The results of the imitation are due to the four imitation processes that the six informants went through, namely the attention process, the retention process, the motor reproduction process, and the motivation process. From the four processes of imitation, we can see the types of imitation based on the imitation efforts made by the six informants, namely the types of direct imitation, indirect imitation, combined imitation, momentary imitation, and continuous imitation.